THE IMPACT OF POLYPHARMACY ON FALL RISK IN PATIENTS WITH PARKINSON’S DISEASE - Eliza Garbacz,; Anastasiia Holoborodko,; Ewa Wieczorkiewicz,; Patrycja Stępińska,; Agnieszka Pocheć,; Bartosz Lautenbach,; Dariusz Nędza,; Klaudia Wojciech,; Anhelina Loputs,; Wiktoria Błaszczyk, (International Journal of Innovative Technologies in Social Science, 2026)
Background: Falls are frequent and disabling in Parkinson’s disease (PD), and polypharmacy may heighten risk through adverse effects such as orthostatic hypotension, sedation, and cognitive decline. However, the specific contribution of multiple medications to fall risk in PD remains underexplored.Aim: This study examined whether polypharmacy increases fall risk in PD and identified medication classes and patient factors influencing this relationship.Methods: In a 12-month prospective cohort, adults with idiopathic PD were evaluated for demographics, PD severity, cognition, comorbidities, orthostatic blood pressure, medication use, and prior falls. Polypharmacy was defined as ≥5 medications and hyper-polypharmacy as ≥10. Falls were tracked monthly. Logistic regression and secondary moderation/mediation analyses assessed predictors of falls.Results: Polypharmacy affected 40–63% of participants and was associated with a higher fall incidence (72.8% vs. 44.8%). It independently increased fall risk (OR = 2.49), with hyper-polypharmacy showing greater impact (OR = 3.11). Benzodiazepines, antipsychotics, antidepressants, and anticholinergics were the strongest medication-related contributors. Older age moderated, and cognitive impairment partly mediated the relationship.Conclusion: Polypharmacy significantly elevates fall risk in PD, particularly when involving CNS-active or anticholinergic drugs. Routine medication review and deprescribing may help reduce falls and improve safety in this population.